Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.5326/0430021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Azathioprine on Lesion Severity and Lymphocyte Blastogenesis in Dogs With Perianal Fistulas

Abstract: Fourteen dogs with perianal fistulas were entered into a prospective clinical study to investigate the effects of long-term azathioprine on clinical outcome and to determine if the clinical results correlated with lymphocyte blastogenesis tests. Complete remission of perianal fistulas was seen in eight (57%) of 14 dogs; partial remission occurred in one (7%) dog; and no response was detected in five (36%) dogs. The results of lymphocyte blastogenesis assays did not correlate with therapeutic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…This result is similar to that in a report in the human literature where time to clinical improvement ranged from 3 to 6 weeks . Remission in dogs with dermatological diseases treated with azathioprine has been reported to be between 3 and 8 weeks, indicating a similar time to effect with MMF . The cases represented in the present study were all dogs that were refractory to immunosuppressive doses of steroids as a monotherapy and, therefore, may represent a subset of patients with severe or unmanageable disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is similar to that in a report in the human literature where time to clinical improvement ranged from 3 to 6 weeks . Remission in dogs with dermatological diseases treated with azathioprine has been reported to be between 3 and 8 weeks, indicating a similar time to effect with MMF . The cases represented in the present study were all dogs that were refractory to immunosuppressive doses of steroids as a monotherapy and, therefore, may represent a subset of patients with severe or unmanageable disease.…”
Section: Discussionsupporting
confidence: 90%
“…No current reports exist describing the use of MMF to treat perianal fistula; however, azathioprine has been used to treat this disease with variable success. One study utilizing azathioprine as a first‐line treatment reported full remission in eight of 13 cases; however, bone marrow suppression was encountered frequently ( n = 5) and was a limiting factor for treatment in some cases ( n = 3) . As MMF has a similar mechanism of action, but a lower tendency to suppress bone marrow, further studies evaluating MMF as a treatment for perianal fistula are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…2002 ). A prospective study performed in 13 German shepherd dogs and one Border collie with perianal fistulas, using a combination of diet, prednisolone and azathioprine, showed that 57% had complete remission after 16 weeks (Harkin et al . 2007 ).…”
Section: Immunosuppressant-responsive Enteropathy In Dogs With Cementioning
confidence: 99%
“…Azathioprin könnte unter Umständen eine kostengünstigere Variante zur Behandlung von Analfissuren darstellen. Die Behandlung führte zu einer Reduktion der Analfissuren, nicht jedoch zu der durch Ciclosporin erreichten Remissionsrate (48).…”
Section: Calcineurin-inhibitoren Ciclosporinunclassified